Role of modality, repetition and age in recognition memory - Amir Kassim, Azlina (2017)
Recognition memory is a part of declarative memory; defined as the ability to discriminate previously presented stimuli from novel stimuli (Squire, Wixted & Clark, 2007). This thesis reports eight experiments that investigated factors that modulate recognition memory using a recognition memory paradigm that reflects the space learning effect (Greene, 1989) and repetition. Results from chapter two varied the space between stimuli repetition across two presentations and found that stimuli that is repeated following a short delay, and then repeated again following a longer delay led to poorer recognition memory compared to other variations. Additionally, results showed impaired recognition for older adults compared to younger adults for first repetition, but not for the second repetition, where no age effects were found (Experiment 1). Electroencephalography (EEG) technique (Experiment 2) examined the old/new effects (higher mean amplitude for old items compared to new items) pertaining to familiarity, recollection and post-retrieval monitoring through the three signatures commonly found in recognition memory, i.e. FN400, late positive component (LPC) and the late frontal effect (LFE) respectively to understand the underlying processes that supports repetition. Contrary to prior research, results showed an absence of the FN400 and LPC effect. However, with respect to the LFE, there was a reverse old/new effect in the left anterior superior (LAS) region for stimuli repeated for the first time which can be attributed to decision making, memory evaluation, and confidence in line with past literature (Allan et al, 1998; Ally & Budson, 2007; Ally et al. 2008; Dobbins & Han, 2006; Fleck, Daselaar, Dobbins & Cabeza, 2006). Chapter 3 investigated the effects of uni-modal (auditory or visual presented alone) and multi-modal stimuli, i.e. auditory and visual modality presented together (cross-modal), on recognition memory. The results show that unlike visual and cross-modal memory retrieval, repetition does not facilitate auditory recognition memory. The results also show that participants have higher d’ scores in the cross-modal stimuli compared to uni-modal stimuli (experiment 3). Although older participants show benefits with cross-modal stimuli, and with repetition, they still performed poorer compared to their younger counterparts (experiment 4). Chapter four investigated semantic congruency of multi-modal pairs in recognition memory. The results show that this effect only lasts for the first repetition and is absent for subsequent repetitions, for both older and younger adults (experiment 5). ERP results showed the presence of the FN400 old/new effect for trials repeated for the second time in the LAS region indicating recognition may be supported by familiarity for items repeated for the second time. In contraction to past research, there was no LPC or the LFE effects seen (experiment 6). Lastly, chapter five focuses on recognition memory in relation to modality mismatch. Modality mismatch is a situation that arises when information is encountered in a different modality compared to when it was initially presented (Mulligan & Osborn, 2009). The results from chapter five shows that auditory modality impairs recognition when it is either presented initially, or after a short delay. However, auditory presentations with a semantically associated pair (visual), either at initial presentation, or only if its pair was encountered after a short delay, there was no significant effect of modality mismatch at long delay (experiment 7). Results showed an absence of the FN400 effect indicating that FN400 effect is sensitive to perceptual match in line with Tsivilis et. al (2001). Lastly, experiment 8 showed that in the presence of modality mismatch, ERP results suggest that participants may rely on recollection to guide recognition process as seen by the presence of the LPC effect. Furthermore, the LPC also seems to index the amount of information to be retrieved consistent to past research (Fjell, Walhovd & Reinvang, 2005; Vilberg, Moosavi & Rugg, 2006), whereby larger amplitude were seen when the trial was in the cross-modal format compared to uni-modal format. As for the LFE component, the presence of the larger mean amplitude in the superior regions for uni-modal trials repeated for the second time suggests further post-retrieval monitoring associated with retrieval of additional information presented initially. Overall findings of this thesis have explored the factors that affect recognition memory, namely repetition, modality and age, and attempted to determine the underlying processes supporting recognition memory when items are repeated, or pairs of stimuli are semantically associated or modality is mismatched during encoding. This is particularly implicated in learning environments, providing further understanding in how repetition can enhance memory and its effects in environments where incongruent information is received, or repeated information encountered in a different modality.